TRANSPORTASI PUBLIK DAN AKSESBILITAS MASYARAKAT PERKOTAAN - Siti Aminah (Universitas Bandar Lampung, 2018)
Mass or public transportation system is not yet fully accessible by the public. The problem is not only related to a fare matter, but is also due to the continuing development of mass transportation system that does not meet the publics’ real need of mass transportation. In principle, public transportation should openly allow all groups with the society to have access for it; it should especially provide fairness guarantee for the poor.